2019
DOI: 10.3390/s19122733
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Automated Cardiac Health Management with Robust Edge Analytics and De-Risking

Abstract: Remote and automated healthcare management has shown the prospective to significantly impact the future of human prognosis rate. Internet of Things (IoT) enables the development and implementation ecosystem to cater the need of large number of relevant stakeholders. In this paper, we consider the cardiac health management system to demonstrate that data-driven techniques produce substantial performance merits in terms of clinical efficacy by employing robust machine learning methods with relevant and selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…The main tool used to pick up signals was the digital stethoscope, mentioning in 44 articles (IDs = 3, 4, 5, 6, 7, 8, 10,11,13,15,16,17,18,19,20,21,22,23,24,25,26,27,29,30,31,32,33,35,36,37,38,39,42,44,45,46,48,49,50,51,52,53,54,56). The connectivity of digital stethoscopes occurs, in most equipment, by Bluetooth, not over the Internet, and for this reason these equipments are not considered IoT devices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main tool used to pick up signals was the digital stethoscope, mentioning in 44 articles (IDs = 3, 4, 5, 6, 7, 8, 10,11,13,15,16,17,18,19,20,21,22,23,24,25,26,27,29,30,31,32,33,35,36,37,38,39,42,44,45,46,48,49,50,51,52,53,54,56). The connectivity of digital stethoscopes occurs, in most equipment, by Bluetooth, not over the Internet, and for this reason these equipments are not considered IoT devices.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 58 articles selected, 34 works (58.62%,IDs = 1, 2, 5, 6, 10, 19,20,21,22,25,31,32,33,34,35,36,37,39,40,41,42,43,44,46,48,49,50,51,52,53,54,55,56,58) mention care using Machine Learning. Leng et al [30] (36) showed the possible interactions between the electronic stethoscope, the sensor-captured signal decomposition algorithm, machine learning techniques and cardiac sound segmentation.…”
Section: Fq1 -Is There Mention Of Care Using Machine Learning?mentioning
confidence: 99%
See 1 more Smart Citation
“…The most influential privacy metric within the privacy community is -differential privacy [22], which has been intensively investigated [23][24][25][26]. Several researchers, such as Fienberg et al [27], Uhlerop et al [28], and Yu et al [7], have suggested approaches to facilitate sharing of χ 2 values while conforming with -differential privacy parameters.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main challenges in such applications is to protect the sensitive information [3 -4]. In fact, it is demonstrated that automation of cardiac management is plausible under privacy preserving derisking scheme [5]. Privacy along with data security are the main concerns that human-centric systems and application need to concentrate as such systems invariably collect, analyze and infer on human-related information and such information is sensitive in nature [6][7][8].…”
Section: Introductionmentioning
confidence: 99%